DIGITAL BANKING ADOPTION AND FINANCIAL PERFORMANCE: EMPIRICAL EVIDENCE IN INDONESIA - Eskasari Putri; Rofi Febriyani; Muhammad Danang Adriyanto (EKUITAS (Jurnal Ekonomi dan Keuangan), 2026)
Digital transformation in Indonesia’s banking industry continues to evolve, yet its impact on banks’ financial performance remains inconsistent. This study aims to examine the effects of digital banking adoption on profitability, risk-taking, and stock returns. Using a quantitative approach with panel data, this study analyzes nine BUKU III and BUKU IV banks listed on the Indonesia Stock Exchange during the 2015–2024 period employing the Random Effects Model (REM). The results indicate that digital banking does not have a significant direct effect on profitability. However, digitalization was found to significantly increase risk-taking and stock returns. These findings indicate that digital activities drive bank business expansion and enhance investor confidence in the banks’ future growth prospects. Furthermore, the results confirm that the impact of digitalization is reflected more rapidly in risk behavior and market responses than in short-term profitability performance. Thus, to achieve optimal financial performance, the implementation of digital banking must be balanced with sound risk management and long-term business strategies.